If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -8b = 6b + -5 Reorder the terms: 4 + -8b = -5 + 6b Solving 4 + -8b = -5 + 6b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-6b' to each side of the equation. 4 + -8b + -6b = -5 + 6b + -6b Combine like terms: -8b + -6b = -14b 4 + -14b = -5 + 6b + -6b Combine like terms: 6b + -6b = 0 4 + -14b = -5 + 0 4 + -14b = -5 Add '-4' to each side of the equation. 4 + -4 + -14b = -5 + -4 Combine like terms: 4 + -4 = 0 0 + -14b = -5 + -4 -14b = -5 + -4 Combine like terms: -5 + -4 = -9 -14b = -9 Divide each side by '-14'. b = 0.6428571429 Simplifying b = 0.6428571429
| 3x+2y+4z=0 | | 3x+6xy=153 | | 1/2x-9=3/4x-5 | | 7r=9t+3 | | 7x-7y-5x+9y= | | 116-75=x | | (5x+2)-(3x+4)=0 | | 8y-3+8y-3=2y | | 10.08+9y=6 | | -3x-12=o | | 22.5-2y=-5 | | (ln)(y)=.61 | | -7x-2/8=-9 | | (6x-9)-(3x+8)=4(x-11) | | -15x^2+27= | | (y-8)(y-3)= | | 3x+6x+9= | | 8x+4x+12= | | 15x+3y=-6 | | 6(x+5)=3[2(2x-3)+1]+5 | | 5(3x-4)=2-2x | | C=0.75n+140 | | 42y+28x= | | 9x+y=10solvey | | -4v+35=-8v+7(5-2v) | | 3(u-5)-7u= | | 5a+b+0.1c=100 | | 17*17=8*8+x*x | | -23x+13y=-29 | | 1/2(44)-3/5=3/5(44)-5 | | 9p+n=84 | | 4x^2y=5 |